Eosinophilic meningitis due to angiostrongylus cantonensis in children - Hao, Tran Kiem; Chi, Nguyen Thi Diem; Son, Nguyen Huu (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Meningoencephalitis is not a rare disease in children. However, eosinophilic meningitis due to Angiostrongylus cantonensis is unusual in pediatric population. We describe the case of a 12-year-old girl from central zone of Vietnam with eosinophilic meningitis. The patient lived in a rural area, where farming is widespread, and presented with fever and headache. Laboratory results showed peripheral eosinophilia, cerebrospinal fluid white blood cell count 730/mm3 with many of eosinophils, cerebrospinal fluid ELISA positive for Angiostrongylus cantonensis, and blood ELISA positive for A. cantonensis. The presentation was consistent with a diagnosis of A. cantonensis eosinophilic meningitis. The patient recovered fully after administering albendazole (800 mg/day for 2 weeks), and intravenous dexamethasone (0.6 mg/kg/day every 8 hours) and mannitol (1.5 g/kg/day every 8 hours) for the first 3 days, followed by 5 days of oral prednisolone (2 mg/kg/day). Keywords: Angiostrongylus cantonensis, eosinophilic meningitis, children